Penerapan CRM Berbasis Web Pada Toko Bunga Village Flower - dewi, indah kusuma (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2021)
This study aims to design a sales system in which there are customer complaints which apply Customer Relationship Management (CRM) relationship management, which helps customers make complaints at the Village Flower Shop, Data obtained in this system consists of, questionnaire data filled out by customers The method used in this system is SDLC with waterfall modeling. To illustrate the model of this system is the context diagram data flow and Data Flow Diagram (DFD), while the relation uses Entity Relationship Diagram (ERD). The system is designed based on Website, using the PHP programming language, MySQL as its database, qualitative research techniques, by collecting data and information descriptively, testing on this system uses a blackbox. With this research where it is expected that the Flower Flower shop with customers and also improving the quality of service quality to customers, to create customer satisfaction.